Effects of alternative responses on behavior exposed to noncontingent reinforcement. Issue 3 (12th August 2013) - Virues‐Ortega, Javier; Iwata, Brian A.; Fahmie, Tara A.; Harper, Jill M.
<x xml:space="preserve">Abstract</x> Noncontingent reinforcement (NCR) may decrease the frequency of behavior by either inducing satiation or terminating the response–reinforcer contingency (extinction). Another possibility is that the target behavior is replaced by other behaviors maintained by preexisting contingencies. We conducted 2 experiments in which we allowed access to a target response and several alternatives. In Experiment 1, NCR, preceded by contingent reinforcement (CR) for the target, produced a reduction in the target and an increase in the alternatives in 2 subjects with intellectual disabilities. To separate the effects of NCR from the availability of alternative responses, we presented CR conditions to 4 subjects in Experiment 2 with and without the availability of alternatives. The availability of alternatives decreased the target in only 1 subject. Subsequent manipulations showed that reductions in the target were solely a function of NCR for the other 3 subjects. Thus, response competition may have marginal effects on response suppression during NCR.